The profile of the level of endogenous no in migraine sufferers - Saleh, Arman Yurisaldi; Machfoed, Hasan; Kuntoro, Kuntoro (Folia Medica Indonesiana, 2017)
Migraine is a health problem which had big impact. A neurochemistry change in the dura, that is the increase of the amount of nitrite oxide, originated from an excessive NOS (inducible NOS) activation during ictal. Some researchers assume NO as a main cause of the pain intensity in ictal. Migraine diagnosis is guided by the International Headache Society. Hopefully, this examination can be used as a more objective diagnosis in the future. Methode of this research is descriptive analytic. This study to find the level of endogenous exhaled NO on 91 subject, consisting of 30 normal people, 31 interictal, 30 ictal. An exclusion was done previously. A validation equipment and measurement had been done in accordance with American Thoracic Association guidance. The result is level of endogenous exhaled NO on the normal group (median=5), interictal group (median=11), ictal group (median=14). Coefficient correlation between VAS and level endogenous exhaled NO was 0,815. So, there is an increase of the NO endogen level in the normal people, migraine interictal, and ictal. Strong correlation between intensity of pain (VAS) and level endogenous exhaled NO during ictal.